Analyzing the Economic Impact of Foreign Employment on Development Prospective of Nepal - Kharel, Khom Raj; Kharel, Suman (Management Dynamics, 2020)
Foreign employment has become one of the major sources of households’ income for Nepalese society. Nepal has become one of the major labors exporting country. After 1990s, remittance is playing a crucial role for foreign currency earnings and favorable impact on balance of payment situation, to reduce the number of people in the country below the poverty line and ultimately to the economic growth of the nation. This paper tries to examine the economic impact of foreign employment on remittance as well analyze the growth and trends of foreign employment and remittance on development prospective in Nepalese economy. Some descriptive statistics such as percentage, ratio, pie-chart, bar diagram and line chart are used to explain the growth and trends of foreign employment as well as situation of remittance in Nepal. Correlation and linear regression model are used to analyze the impact of foreign employment on remittance. The inflow of remittance growth rate has positive association along with significant contribution of remittance to Gross Domestic Product in Nepalese economy. Also, foreign employment has important effect on remittance. Foreign employment is one of the effective instruments for poverty alleviation and social changes.